Impaired Peripheral Endothelial Function Assessed by Digital Reactive Hyperemia Peripheral Arterial Tonometry and Risk of In‐Stent Restenosis. Issue 6 (17th June 2016) - Komura, Naohiro; Tsujita, Kenichi; Yamanaga, Kenshi; Sakamoto, Kenji; Kaikita, Koichi; Hokimoto, Seiji; Iwashita, Satomi; Miyazaki, Takashi; Akasaka, Tomonori; Arima, Yuichiro; Yamamoto, Eiichiro; Izumiya, Yasuhiro; et al.
Abstract : Background: Drug‐eluting stents are replacing bare‐metal stents, but in‐stent restenosis (ISR) remains a problem. Reactive hyperemia index (RHI) assessed by peripheral arterial tonometry evaluates endothelial function noninvasively. We prospectively assessed the prognostic value of RHI in predicting ISR after percutaneous coronary intervention. Methods and Results: RHI was measured before percutaneous coronary intervention and at follow‐up (F/U) angiography (F/U RHI; 6 and 9 months post bare‐metal stents– and drug‐eluting stents– percutaneous coronary intervention, respectively) in 249 consecutive patients. At F/U, ISR (stenosis >50% of diameter) was seen in 68 patients (27.3%). F/U natural logarithm (RHI) was significantly lower in patients with ISR than in those without (0.52±0.23 versus 0.65±0.27, P <0.01); no between‐group difference in initial natural logarithm (RHI) (0.60±0.26 versus 0.62±0.25, P =0.56) was seen. By multivariate logistic regression analysis, even after adjusting for other significant parameters in univariate analysis, F/U natural logarithm (RHI) independently predicted ISR (odds ratio: 0.13; 95% CI: 0.04–0.48; P =0.002). In receiver operating‐characteristic analysis, F/U RHI was the strongest predictor of ISR (area under the curve: 0.67; 95% CI: 0.60–0.75; P <0.01; RHI <1.73 had 67.6% sensitivity, 64.1% specificity); area under the curve significantly improved from 0.62 to 0.70 when RHI was added to traditional ISR risk factors ( P =0.02). Net reclassification index was significant after addition of RHI (26.5%, P =0.002). Conclusions: Impaired RHI at F/U angiography independently correlated with ISR, adding incremental prognostic value to the ISR‐risk stratification following percutaneous coronary intervention. Clinical Trial Registration: URL:https://www.clinicaltrials.gov/ . Unique identifier: NCT02131935.